Gastronomy experiential traits and their effects on intentions for recommendation: a fuzzy set approach - Correia, Antónia (2020)
Local food is a motivation that drives international tourists to visit a certain destination and to enrich their experiential quality. Although considerable effort has been exerted in investigating the relationship between the importance of local food and satisfaction and future intentions, no study has explored gastronomical experience by using fuzzy set analysis. The present study aims to explore the influence of local food attributes on customer satisfaction and intentions to recommend through a fuzzy set analysis. This study uses empirical data from 1,376 international tourists visiting Hong Kong. Findings suggest that the attributes of local food and their influence on the intentions to recommend vary in accordance with the type of restaurants operating in Hong Kong. The results of this study shed practical implications, such as the development of different symbolic meanings of gastronomy and service for international diners at different restaurants.